(untitled) (Revista de Ciências Agroveterinárias, 2019)
Native pastures are very important food sources for bovine and sheep production in the Pampa biome. Ryegrass introduction and nitrogen fertilization are alternatives aimed at a more sustainable intensification of livestock production. The objective of this study was to evaluate the effects of doses of nitrogen fertilizer in native pasture with ryegrass introduction on soil chemical acidity indicators. The experiment consists of a secondary native pasture under continuous grazing. The area was limed, and three different nitrogen rates (0, 100, and 200 kg ha-1 year-1 of nitrogen) were applied. Basis and aluminum saturation and pH were evaluated in 0-10 and 10-20 cm soil layer. In 0-10 cm soil layer, pH decreases 0.27 units per 100 kg ha-1 year-1 of nitrogen applied. In 10-20 cm soil layer, pH decreases of 5.3 to 4.7 and 4.6 with dose of nitrogen of 100 and 200 kg ha-1 year-1, respectively. Long-term nitrogen fertilization in native pasture with ryegrass introduction resulted in soil acidification until 20 cm soil depth.